The biology of streams as part of Amazonian forest ecology - Walker, Ilse (Experientia, 1987)
Data on long-term research on the ecology of Central Amazonian forest streams are presented and they reveal the following basic features: Firstly, the essential input of nutrients into these waters consists of forest litter and of the fungi that decompose this litter; consequently, the bulk of the fauna is concentrated in accumulations of submerged litter. Secondly, the nutrients released by the decomposition of this litter do not appear in solution in the stream water, but are tied up throughout in the food web of the aquatic fauna. Thirdly, this food web is relatively robust. This is due to the absence of food specialists in the major channels of energy transfer. One of the staple foods for invertebrate predators consists of chironomid larvae. Fourthly, the degree of acidity and/or the content of dissolved humic substances (more or less black water) has a marked effect on the density and to a lesser extent on the species diversity of the invertebrate fauna, black waters being richer in both. Fifthly, the annual inundations of the forest in the middle and lower courses of the smaller rivers lead to drastic periodic changes of animal densities, and in some cases to annual periodicity of breeding, as exemplified by a three-year study of shrimp populations in the river 'Tarumazinho'. © 1987 Birkhäuser Verlag.